Enhanced thermal conductivity of graphene nanoplatelet filled polymer composite based on thermal percolation behavior. (April 2022) - Jang, Ji-un; So, Soon Oh; Kim, Jong Hyeok; Kim, Seong Yun; Kim, Seong Hun
Abstract: The demand for lightweight heat-dissipating composites has increased interest in strategies to improve the thermal conductivity of polymer composites by incorporating nanocarbon fillers. In this study, composite incorporating uniformly dispersed high content (∼50 wt%) of graphene nanoplatelet was fabricated with low-viscosity polyamide 6 (PA6) resin. The measured thermal conductivity of the composite exhibited thermal percolation when GNP content exceeded 30 wt%, and the in-plane thermal conductivity improved to 19.39 W/m·K (1315% increase compared to neat PA6) at the filler content of 50 wt%. In addition, thermal conductivity of the prepared composites was in good agreement with theoretical results based on Nan's model (filler content of 0–30 wt%) considering interfacial thermal resistance and the percolation equation (filler content of 40–50 wt%) considering a connected filler network. It was confirmed that thermal percolation was generated due to contacts and network formation between fillers in the fabricated composites using an internal structure analysis. Potential insights on the design, manufacture, and application of nanocomposites exhibiting heat dissipation performance can be provided by composite systems using low-viscosity resin and theoretical evaluation methods. Graphical abstract: Image 1 Highlights: Composite containing high content of uniformly dispersed GNP was fabricated. Above 30 wt% GNP loading, thermal percolation behavior occurred. Thermal conductivity results were interpreted by Nan's and percolation models. The connected filler network resulted in thermal percolation behavior.